Relationship Of 25(Oh)D Umbilical Levels With Neonatal Hyperbilirubinemia - Jeanette I. Ch. Manoppo; Rocky Wilar; Felicia Halim; Ernestine Vivi Sadeli (Syntax Corporation Indonesia, 2023)
The purpose of this study was to determine the relationship between vitamin D levels in the umbilical cord with the occurrence of hyperbilirubinemia in neonates. This study used an analytical observational design in a cohort prospective. This study compared two groups based on the results of vitamin D measurements. Each group, then followed up to examine the occurrence of hyperbilirubinemia. This research will be conducted from October 2022 to January 2023. Sample selection is done by consecutive sampling technique. RESULTS: Of the 19 or 79.2% of infants with 25-hydroxy-vitamin D deficiency, they had hyperbilirubinemia. While in the group that did not experience deficiency, only 3 or 10.7% experienced hyperbilirubinemia. There was a difference in the incidence of hyperbilirubinemia between infants who had 25-hydroxy-vitamin D deficiency compared to those without 25-hydroxy-vitamin D deficiency, with an RR of 6.71, which was statistically significant (p<0.001). 25-hydroxy- vitamin D deficiency was shown to be a factor associated with hyperbilirubinemia with an adjusted RR of 6.63. In conclusion, there is a strong relationship between 25(OH)D levels in the umbilical cord and neonatal hyperbilirubinemia, where 25(OH)D deficiency is a risk factor for hyperbilirubinemia. Neonates with 25(OH)D deficiency are 6.63 times more likely to develop hyperbilirubinemia than those without 25(OH)D deficiency